SmartSlog session scheme for smart-M3 applications - Aleksandr Lomov (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2012)

(untitled)
Smart spaces provide a shared view of dynamic resources and context-aware services within a distributed application. Smart-M3 is an open-source platform that implements the smart space concept. It inherits the tuplespace and publish/subscribe asynchronous communication models, and agents (Smart-M3 knowledge processors, KPs) cooperate sharing the common smart space. A SmartM3 semantic information broker (SIB) maintains the smart space in low-level ontological terms of triples. Smart Space Access Protocol (SSAP) is used for session management and triple governance transactions. This paper considers the session between KP and SIB in the Smart-M3 applications. First, SSAP session will be studied. Second, a new SmartSlog session scheme will be introduced. It operates with such ontological concepts as a class, a property, and an individual and extends the capabilities of SSAP session. New session scheme is based on SSAP session and can manipulates with many SSAP sessions by combining them in one session. All data are shared between SSAP sessions and it allows to work with different smart spaces as with one on KP side. The new session scheme is partially implemented in SmartSlog ontology library.